Problems of Ecological and Economic Transformation of Natural Management Systems and Territories: Example of the South of Russia - Dovgot'ko, Natal'ja Anatol'evna; Kusakina, Olga Nikolaevna; Rjazancev, Ivan Ivanovich; Cherednichenko, Olga Alexandrovna; Kaznacheeva, Olga Harlampievna (International Journal of Economics and Financial Issues, 2016)
This paper shows the crucial importance of taking into account ecological factor in the economic development of modern countries and territories. Through the example of the southern regions of Russia the issues of ecological and economic transformation of natural management systems and the development of the economic mechanism taking into account the threshold of ecological safety are explored. The main problematic areas of natural resource use in the southern regions of Russia are identified, and the author's vision of the conceptual model of the mechanism of rational use of natural resources with regard to ethno-cultural traditions such as natural management of the territory, as well as international experience is proposed. The ways of improving the organizational-economic mechanism of natural resource use on the basis of system accounting of natural resource rent and stimulation of rational use of natural resources are offered. Keywords: ecological and economic transformation, natural resource use, ecological safety, green economy, sustainable development JEL Classifications: Q57, Q56, Q58, O13.